Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1999)
Table of Content Surface to Air – The Collage Paintings of Donald Bachler Doug Aitken Omega Man by James Roberts Liquid Time by Francesco Bonami Doug Aitken, the Stalker of this Fin de Siècle by Christine van Assche Nan Goldin On the Edges of the Image by Elisabeth Lebovici Between Worlds – Nan Goldin’s Recent Photographs by Arthur C. Danto Christine Floating in the Sea, 1999 by Lisa Liebmann The Party’s Over by Dana Friis-Hansen Images of Intimacy by Ulmann-Matthias Hakert Suzanne and Philippe on the Train, Long Island 1985 by Deborah Eisenberg Thomas Hirschhorn Thomas Hirschhorn by Robert Fleck Cheap Tricks – Hirschorn’s Transvaluation Machine by Alison Gingeras Thomas Hirschhorn, Your Are So Annoying by Philippe Vergne Reason in Conflict – The War of Différance II by Thomas Steinweg Louise Lawler – Specters of Modernity by Andrea Kroksnes John Miller by Lionel Bovier Fernando Melani: Art and Habitat, Les Infos du Paradis by Rudolf Schmitz Retrace Your Steps : Remember Tomorrow, An Exhibition in Sir John Soane’s Museum, Cumulus from Europe by Hans Ulrich Obrist West of Everything, Cumulus from Europe by Connie Butler
The museum door on the back cover has also been transported into the realm of anonymous personal expression with tags and stickers from Hirschhorn’s own inventory. In addition, this volume of Parkett has a surprise in store: contrary to custom, the layout of Thomas Hirschhorn’s section has been designed by the artist himself. (editorial by publisher)
boek
Keywords: Aitken, Doug; Hirschhorn, Thomas; Goldin, Nan